Wczesne rozpoznawanie zaburzeń ze spektrum autyzmu – symptomy ryzyka, diagnoza wstępna, badania przesiewowe - WINCZURA, BARBARA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Barbara Winczura, Wczesne rozpoznawanie zaburzeń ze spektrum autyzmu – symptomy ryzyka, diagnoza wstępna, badania przesiewowe [Early detection of autism spectrum disorders – risk symptoms, initial diagnosis, screening]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 73-103. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.05 The diagnosis of autism within the first two years of a child’s life is burdened by many difficulties. The most significant symptoms for early recognition of ASD are deemed to be emotional and social deficits, disturbances in the development of speech and communication as well as atypical behaviour in the form of limited, repetitive behaviour patterns. In the first as well as the second year of life, the most commonly confirmed early signs of ADS refer to the lack of behaviour indicating the child’s readiness to form social relations and to social communication, including in particular its reactions to its own name, limited eye contact, atypical facial expressions in social situations, the lack of emotional adaptation, limited interest in social impulses and poor vocalisation, as well as limited abilities to imitate, establish a common field of attention and the expression of attachment to the next of kin. In the second year of age, the atypical behaviour is manifested more clearly and may, although it must not necessarily, shine through in all areas typical for autism.